Testing the functionality of peripheral vision in a mixed-methods football field study - Vater, C.; Luginbühl, S.; Magnaguagno, L. (Journal of Sports Sciences, 2019)
In team sports, peripheral vision might be useful to simultaneously monitor movements of opponents and teammates. Until now, however, little is known about the perceptual-cognitive processes underlying peripheral vision in a sporting task. Therefore, we used a mixed-methods approach with in-situ decision making (3 vs. 3 situations) and retrospective verbal reports to identify perceptual strategies used for optimal information pick-up in high- and low-skilled football players. Our results show that the use of peripheral vision by central defenders depends on the position of the ball and the position of the direct opponent. Players were shown to either use a pivot strategy, whereby they frequently look at the direct opponent if he is not in the possession of the ball in addition to making saccades to monitor other players, or they employ a more direct strategy, in which gaze is anchored on this location, avoiding saccades and monitoring the other players with peripheral vision. Based on our findings we make recommendations about how these gaze strategies can be further tested in future research and how sports practice can benefit from these results.